Au-courant and novel technologies for efficient doubled haploid development in barley (Hordeum vulgare L.). (19th May 2023) - Patial, Madhu; Chauhan, Ruchi; Chaudhary, Harinder K.; Pramanick, Kallol K.; Shukla, Arun K.; Kumar, Vishnu; Verma, Ramesh P. S.
Abstract: Bounteous modern and innovative biotechnological tools have resulted in progressive development in the barley breeding program. Doubled haploids developed (homozygous lines) in a single generation is significant. Since the first discovery of haploid plants in 1920 and, in particular, after discovering in vitro androgenesis in 1964 by Guha and Maheshwari, the doubled haploidy techniques have been progressively developed and constantly improved. It has shortened the cultivar development time and has been extensively used in: genetic studies, gene mapping, marker/trait association, and QTL studies. In barley, the haploid occurrence developed gradually from being a sporadic and random process (spontaneous) to haploid development by in vivo method of modified pollination or by in vitro culture of immature male or female gametophytes. Although significant improvement in DH induction protocols has been made, challenges still exist for improvement in areas such as: low efficiency, albinism, genotypic specificity etc. Here, the paper focuses on: haploidization via different in vitro, in vivo techniques, the recent advances technologies like centromere‐mediated haploidization, hap induction gene, and Doubled haploid CRISPR. The au-courant work of different researchers in barley using these technologies is reviewed. Studies on different factors affecting haploid induction and work on genome doubling of barley haploids to produce DH lines via spontaneous and induced technologies has also been highlighted.